(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2023)
Agile and Traditional IT Project Management both have pros and cons for managingcomplicated projects. Agile teams can quickly adjust to new needs due to its flexibility and iterativenature. Collaboration, customer input, and gradual progress reduce the risk of producing a product thatdoesn’t fulfil user demands. However, its informality may cause scope creep and uncertainty aboutschedules and prices. This article compares agile and conventional IT project management.